A proposed preamble channel estimation scheme for flip FBMC-based indoor VLC systems - El-Ganiny, Mohamed Y.; Khalaf, Ashraf A. M.; Hussein, Aziza I.; Hamed, Hesham F. A. (Opto-Electronics Review, 2022)
Filter bank multicarrier waveform is investigated as a potential waveform for visible light communication broadcasting systems. Imaginary inter-carrier and/or inter-symbol interference are causing substantial performance degradation in the filter bank multicarrier system. Direct current-biased optical filter bank multicarrier modulation overcomes all the problems of direct current-biased optical-orthogonal frequency division multiplexing modulation approaches in terms of speed and bandwidth. However, it also wastes a lot of energy while transforming a true bipolar signal into a positive unipolar signal by adding direct current-bias. In this paper, a flip-filter bank multicarrier-based visible light communication system was introduced to overcome this problem. In this system, a bipolar signal is converted to a unipolar signal by isolating the positive and negative parts, turning them to positive and then delivering the signal. Also, a new channel estimation scheme for a flip-filter bank multicarrier system is proposed which improves the channel estimation performance compared to that of each of the conventional schemes. The proposed system performance is measured in terms of bit error rate, normalized mean squared error, and constellation diagram. The superiority of the proposed scheme over other conventional structures has been successfully verified by MATLAB 2020b simulation experiments results. These results are evaluated under indoor visible light communication standard.